Spillover in European and South American integration. - Malamud, Andrés (2006)
Spillover is a concept coined by neo-functionalism in the 1960s in order to account for the process of European integration. It refers to the inner dynamics whereby the members of a regional scheme would be compelled to either enlarging the scope or increasing the level of their mutual commitments or both. However, Latin American integration processes have questioned the meaningfulness and applicability of the concept, both in its political and technical dimensions. Through a comparison between the European Union, the Andean Community and Mercosur, this paper looks into the reasons why this happened, addressing conceptual as well as empirical matters.